Competency support for digital transformation mechanisms in public administration: institutional and applied aspects - Sikalo , Maksym (Theory and Practice of Public Administration, 2026)
Digital transformation of public administration is reshaping not only the tools used by civil servants, but also the logic of decision-making itself. Consequently, the competencies required for effective performance differ substantially from those captured by existing international frameworks. This article examines the institutional and applied conditions for the development of digital competencies among public servants, taking into account crisis settings, high uncertainty, and the integration of artificial intelligence systems into managerial processes. Particular attention is given to the phenomenon of the “digital facade,” whereby e-services are introduced without corresponding changes in managerial practices, which makes competency assessment through formal indicators of training coverage inadequate. It is argued that the competencies of public servants cannot be transferred mechanically across institutional systems; rather, their formation requires adaptation to the specific managerial environment and regulatory conditions. The study demonstrates that the three leading international frameworks – DigComp 2.2, the UNESCO AI Competency Framework, and the OECD Skills for Digital Government – do not treat the value-based and resilience dimensions as independent analytical units, which significantly limits their applicability in transitive and crisis contexts. The non-compensatory nature of competency dimensions is also substantiated: a deficit in one dimension cannot be offset by an excess in another, and this directly affects the effectiveness of digital transformation mechanisms. Accordingly, a correspondence matrix has been developed to align competency dimensions with public administration mechanisms, as well as competency profiles by level of governance and functional role. The findings of the study may be used to improve civil servant training systems, develop competency profiles in the field of digital governance, construct individualized professional development pathways, and diagnose competency gaps within public authorities.